Analyzing Profitability, Leverage, and Company Size on Tax Avoidance: Literature Review - Lina Rosyidah; Sri Trisnaningsih (International Journal of Management Research and Economics, 2024)
Paying taxes is a citizen's responsibility. According to Tax Law Number 28 article 1, 2007 (KUP), tax is a payment obligation carried out by individuals or legal entities to the state without compensation, and is used to meet tax needs managed by the state. But on the other hand, companies are organized to obtain maximum profits. Differences in the interests of taxpayers and the government can lead to tax avoidance. Several cases also occurred in Indonesia. This research was designed based on the results of a literature review. The aim is to find and assess three components that have the potential to influence tax avoidance. The methodology encompasses a systematic literature review of six articles from Sinta or Garuda indexed journals, all addressing the same topic and published within the past two years. The study's findings suggest that financial leverage, profitability, and the size of a company influence tax avoidance. The aim of this literature review is to deepen understanding and broaden viewpoints regarding the elements that can impact tax avoidance.